THE EFFECTIVENESS OF RESTORATIVE JUSTICE FOR VICTIMS OF NARCOTICS CRIME - Zainuddin; Alifuddin, Moj; Talib, Hambali (Fakultas Hukum Universitas Djuanda, 2024)
The aim of this research is to analyze the effectiveness of implementing restorative justice for victims of drug-related crimes and the factors influencing the effectiveness of restorative justice for these victims at Polrestabes Makassar. This empirical legal research was conducted at Polrestabes Kota Makassar. The research utilized both primary and secondary data, and data collection techniques involved interviews. The data analysis was performed using qualitative descriptive analysis. The research findings indicate that the application of Restorative Justice at Polrestabes Makassar is quite effective in terms of the quantity of drug-related cases resolved. The significant factors contributing to the effectiveness of Restorative Justice include adequate psychological and social support, collaboration with relevant institutions, and a legally-based approach.